К вопросу оценки ресурса высокотемпературных узлов турбоагрегата - Пугачева, Т. Н. (НТУ "ХПИ", 2017)
Розглянуті питання, пов'язані з визначенням залишкового ресурсу служби високотемпературних вузлів турбоагрегату. Проаналізовані фактори, що визначають тривалість надійної експлуатації турбоустановки: вичерпання тривалої пластичності із-за повзучості матеріалу; накопичення пошкоджень в критичних зонах роторів із-за малоциклової втоми.

The issues has been treated connected of determination of residual resource of service of high temperature knots of turbine. Factors determining duration of reliable exploitation of turbineare analysed: exhausting of the protracted plasticity from the creep of material; accumulation of damages in the critical areas of rotors because of a cyclic alfatigue.
To the problem of high-temperature elements of turbine
Keywords: высокотемпературная ползучесть металла; турбоустановки; исчерпание ресурса; малоцикловая усталость; паровые турбины; напряженно-деформированное состояние